Konseling Sufistik sebagai Upaya Pengembangan Fitrah Manusia - Halimatus Sakdiah; Ilham Ilham; Muhammad Wildan; Muhammad Rif’at (Al-Hiwar Jurnal Ilmu dan Teknik Dakwah, 2023)
Human nature is a gift from God that must be well-developed. Sufistic counselling is an alternative to developing human nature. The purpose of this study is to explain the importance of Sufistic counselling in developing human nature. The research method used is the literature method with a qualitative approach. Data collection techniques using literature study.Data analysis technique using content analysis. The results of the study show that Sufistic counselling as a counselling approach can help develop human nature as well as solve various problems faced by the Sufism approach. Sufistic counselling can help people realize their existence as creatures of God and also as caliphs of God, help develop religious nature and make people closer to God.